2009
DOI: 10.1007/s00421-009-1116-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term endurance exercise training on vascular function in young males

Abstract: We investigated effects of 6 days of endurance exercise training [cycling at 65% of peak oxygen consumption (VO(2peak)) for 2 h a day on six consecutive days] on vascular function in young males. Measures of VO(2peak), arterial stiffness, calf vascular conductance and heart rate variability were obtained pre- and post-training. Indices of arterial stiffness were obtained by applanation tonometry to determine aortic augmentation index normalized to a heart rate of 75 bpm (AI(x) at 75 bpm), and central and perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
6
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 52 publications
0
50
6
3
Order By: Relevance
“…Shorter but more intense endurance cycling (6 consecutive days for 2 h per day) resulted in significant reductions in central and peripheral PWV but no change in AIx. 34 Thus, changes in arterial lumen diameter may only be brought about by prolonged training lasting longer than 6 days. Given that arterial stiffness increases with age future studies utilizing prolonged exercise are needed to examine whether aerobic exercise is also beneficial for middleaged and older individuals.…”
Section: Augmentation Indexmentioning
confidence: 99%
“…Shorter but more intense endurance cycling (6 consecutive days for 2 h per day) resulted in significant reductions in central and peripheral PWV but no change in AIx. 34 Thus, changes in arterial lumen diameter may only be brought about by prolonged training lasting longer than 6 days. Given that arterial stiffness increases with age future studies utilizing prolonged exercise are needed to examine whether aerobic exercise is also beneficial for middleaged and older individuals.…”
Section: Augmentation Indexmentioning
confidence: 99%
“…Land-based aerobic exercise training has been shown to effectively improve AS in healthy individuals and in patients with CVD (Currie, Thomas, & Goodman, 2009;Donley et al, 2014;Moreau, Donato, Seals, DeSouza, & Tanaka, 2003;Hirofumi Tanaka, DeSouza, & Seals, 1998;Tanaka et al, 2000). Further, aquatic-based exercise training (swimming) has been shown to improve arterial compliance and blood pressure (Nualnim et al, 2012).…”
mentioning
confidence: 99%
“…On the other hand, some other studies (Kingwell et al, 1997;Currie et al, 2009;Jae-Bin et al, 2013) found that whole body arterial Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jbiomech www.JBiomech.com compliance (WBAC) and then arterial distensibility was increased after cycling and treadmill exercise with relation to the values prior to exercise. This is a different result that compares arterial distensibility before and after the period in which heart rate is increased.…”
Section: Introductionmentioning
confidence: 95%